Hadis-Hadis Toleransi Beragama dalam Perspektif Kitab Shahih Bukhari dan Shahih Muslim - Abdul Muhyi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Religious Tolerance: on the background of the many people who do not understand the existence of differences, appreciate understandings that are different from their own, which leads to an open attitude and accepts various kinds of differences, both in terms of ethnicity, nation, skin color, customs, culture and religion. This is all the sunnatullah that has become his stipulation. Based on the background above, the formulation of the problem in this thesis are: 1. What is Religious Tolerance in Islam, 2. What is Religious Tolerance in the Study of the Books of Sahih Bukhari and Sahih Muslim, 3. How are the differences in the quality of Hadith in the Books of Sahih Bukhari and Sahih Muslim. The objectives of this research are: 1. To find out the understanding of religious tolerance in Islam, 2. To find out the general description of religious tolerance in the two books in more depth, 3. To help provide an understanding of the differences in the quality of hadith between the books of Sahih Bukhari and Sahih Muslim regarding religious tolerance. The research model used in this research is qualitative research, which produces descriptive research using literary sources. Researchers also use the thematic method. The findings of this study: Religious tolerance, found in Q.S. Al-Kafirun: 109/ 1-6, and there is a hadith explaining religious tolerance in H.R. Muslim: 2564, volume 4, page 1987, H.R. Al-Bukhari: 39, Volume 1, Page 17 and H.R. Al-Bukhari: 2076, Volume 3 Page 57. The similarity point of the hadiths of authentic bukhari and authentic Muslim is that there is no compulsion to embrace Islam, do not commit violence or ridicule among fellow Muslims or non-Muslims, while the difference is that the hadith is about religious tolerance there are more in bukhari traditions than in Muslim traditions, and also explain both rationally and practically.